2012
DOI: 10.1111/j.1440-1681.2011.05659.x
|View full text |Cite
|
Sign up to set email alerts
|

Stat3: Linking inflammation to (gastrointestinal) tumourigenesis

Abstract: Tumourigenesis is a multistage process comprising initiation, promotion and progression that is governed by cumulative (epi-)genetic changes. However, tumour initiation, triggered by mutations in proto-oncogenes and/or tumour suppressor genes, is insufficient for the development of cancers. Tumour promotion often depends on the interaction between initiated cells and the microenvironment where an excessive abundance of inflammatory mediators, including those of the interleukin (IL-)6/glycoprotein 130 (gp130) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 92 publications
(184 reference statements)
1
27
0
Order By: Relevance
“…Furthermore, it was shown that low-grade intraepithelial lesions in Stat3-deficient mice progress to advanced tubular tumors, thus, affirming the critical role of STAT3 in IEC proliferation and survival in CAC carcinogenesis (92). Additionally, more aggressive tumors have been observed in relation to STAT3 activation, either by epithelial-specific SOCS3 ablation or introduction of SOCS3 binding-deficient gp130 Y757F mutation (93,94). These reports have provided valuable insights into STAT3-driven inflammation and gastric cancer (94).…”
Section: Jak-stat Signaling In Gastric Carcinoma Various In Vitromentioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore, it was shown that low-grade intraepithelial lesions in Stat3-deficient mice progress to advanced tubular tumors, thus, affirming the critical role of STAT3 in IEC proliferation and survival in CAC carcinogenesis (92). Additionally, more aggressive tumors have been observed in relation to STAT3 activation, either by epithelial-specific SOCS3 ablation or introduction of SOCS3 binding-deficient gp130 Y757F mutation (93,94). These reports have provided valuable insights into STAT3-driven inflammation and gastric cancer (94).…”
Section: Jak-stat Signaling In Gastric Carcinoma Various In Vitromentioning
confidence: 82%
“…In particular, aberrant STAT3 expression has been implicated in gastric adenocarcinoma patients, making STAT3 a promising candidate as a prognostic marker in gastric cancers (79,85,125,126). In gastric cancer, the abnormal STAT3 expression not only contributes to cancer cell proliferation and survival, but also functions in promoting inflammation, EMT transition and metastasis (94,97,127,128). Various in vitro and in vivo studies have confirmed the role of STAT3 in the precancerous pathology of the stomach, indicating that STAT3 may serve as a useful prognostic/diagnostic biomarker for the early detection of gastric cancer and that limiting STAT3 activity could help prevent malignancy (125).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the induction of JAK/STAT3 activation appears most critical in GI tumorigenesis (32). To investigate whether IL-11 is sufficient to induce STAT3 activation in isolated wild-type epithelium, we incubated primary epithelial crypts isolated from mouse small intestine with recombinant IL-11.…”
Section: ;Ampka2mentioning
confidence: 99%
“…The initial activation of NF-kB by inflammatory signals activates a self-reinforcing regulatory circuit that comprises IL-6 and Stat3 and converts a stable normal cellular phenotype into a stable neoplastic phenotype without any change in DNA sequence (Iliopoulos and others 2009), linking tumorigenesis to NF-kB activation and inflammation (Ernst and Putoczki 2012).…”
Section: Figmentioning
confidence: 99%